Synthesis and antiviral activity of 4,6-disubstituted pyrimido[4,5-b]indole ribonucleosides - Tichý, Michal; Pohl, Radek; Xu, Hao Ying; Chen, Yen-Liang; Yokokawa, Fumiaki; Shi, Pei-Yong; Hocek, Michal (Bioorganic & medicinal chemistry, 2012)
A series of new pyrimido[4,5-b]indole ribonucleosides bearing phenyl or hetaryl group at position 4 has been prepared by selective Pd-catalyzed cross-coupling reactions of the corresponding protected 4,6-dichloropyrimido[4,5-b]indole ribonucleoside with (het)arylboronic acids or stannanes followed by deprotection. Further cross-couplings under harsher conditions and employing X-Phos ligand proceeded at the position 6 leading to 4,6-disubstituted pyrimido[4,5-b]indole ribonucleosides. Some of these compounds displayed antiviral activity against Dengue virus.
Keywords: ribonukleosidy; Ribonucleosides; indoly; palladium; Humans; Catalysis; Indoles; pyrimidiny; Palladium; Dengue Virus; lidé; proliferace buněk; Hep G2 Cells; Virus Replication; buňky Hep G2; antivirové látky; Cell Proliferation; replikace viru; Antiviral Agents; nádorové buněčné linie; virus dengue; Cell Line, Tumor; Pyrimidines; Hepacivirus; katalýza